Association Between Farm Machinery Operation and Low Back Disorder in Farmers: A Retrospective Cohort Study. Issue 6 (June 2016) - Essien, Samuel Kwaku; Bath, Brenna; Koehncke, Niels; Trask, Catherine
Abstract : Objective: The association between whole body vibration (WBV) as measured by annual accumulated use of all-terrain vehicles (ATV)/combine/tractor operation and low back disorders (LBDs) among farmers was investigated. Methods: Saskatchewan Farm Injury Cohort Study data was used. Baseline data were collected in 2007 on the three vehicle types and other factors. Follow-up data on LBD symptoms were collected during 2013 resulting in 1149 samples. Results: Adjusted for age, education, and gender, LBDs were associated with tractor operation for 1 to 150 hours/year (Relative Risk [RR] = 1.23, 95%CI 1.05 to 1.44), 151 to 400 hours/year (RR = 1.32, 95%CI 114 to 1.54) and 401+ hours/year (RR = 1.34, 95%CI 1.15 to 1.56). Additionally, hip symptoms were associated with tractor operation. Only unadjusted associations were found in combine and ATV operation. Conclusions: Duration of tractor operation and older age are important predictors of both low back and hip symptoms in farmers.